2021
DOI: 10.3390/nano11082146
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitectonics for Hierarchical Fullerene Nanomaterials

Abstract: Nanoarchitectonics is a universal concept to fabricate functional materials from nanoscale building units. Based on this concept, fabrications of functional materials with hierarchical structural motifs from simple nano units of fullerenes (C60 and C70 molecules) are described in this review article. Because fullerenes can be regarded as simple and fundamental building blocks with mono-elemental and zero-dimensional natures, these demonstrations for hierarchical functional structures impress the high capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 178 publications
0
12
0
Order By: Relevance
“…In this review paper, the biomedical effects of fullerenes were described in the context of fullerenes to nanoparticles. Fullerenes are zero-dimensional carbon allotropes that serve as a basic unit that can be transformed into one-dimensional structures [ 176 , 177 ], two-dimensional morphologies [ 178 , 179 ], three-dimensional motifs [ 180 , 181 ], and even more complex hierarchical structures [ 182 , 183 ]. In fact, some studies have reported the two-dimensional arrangement of one-dimensional structures, such as fullerene nanowhiskers that demonstrate control over cell growth and differentiation [ 184 , 185 , 186 ].…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…In this review paper, the biomedical effects of fullerenes were described in the context of fullerenes to nanoparticles. Fullerenes are zero-dimensional carbon allotropes that serve as a basic unit that can be transformed into one-dimensional structures [ 176 , 177 ], two-dimensional morphologies [ 178 , 179 ], three-dimensional motifs [ 180 , 181 ], and even more complex hierarchical structures [ 182 , 183 ]. In fact, some studies have reported the two-dimensional arrangement of one-dimensional structures, such as fullerene nanowhiskers that demonstrate control over cell growth and differentiation [ 184 , 185 , 186 ].…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…2 ). According to their shape, size and dimension, carbon nanomaterials 12,13 can be divided into zero-dimensional nanomaterials (buckminsterfullerene 14 and carbon dots (CDs) 15 ), one-dimensional nanomaterials (CNTs 11 and carbon nanofibers (CNFs) 16 ), two-dimensional nanomaterials (graphene 17,18 ) and three-dimensional nanomaterials such as carbon sponges 1,19,20 ( Fig. 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well-accepted that MWCNTs are among the most preferred carbon-based nanomaterials for electrode modification due to their stability, excellent mechanical and conductive properties, low cost, and high surface area. 19 , 21 23 In addition, Fe 2 O 3 NPs can improve electron transfer kinetics, high surface area, biocompatibility, and nontoxic profile, and they are used to improve the catalytic performance of electrochemical systems. 23 , 27 In addition, chitosan, as a natural polymer with high stability, biocompatibility, affordability, and ability to construct film matrixes, is widely preferred to be employed in combination with various nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 21 23 In addition, Fe 2 O 3 NPs can improve electron transfer kinetics, high surface area, biocompatibility, and nontoxic profile, and they are used to improve the catalytic performance of electrochemical systems. 23 , 27 In addition, chitosan, as a natural polymer with high stability, biocompatibility, affordability, and ability to construct film matrixes, is widely preferred to be employed in combination with various nanomaterials. 27 , 28 Taken together, due to the unique electrical and optical properties of MWCNTs, Fe 2 O 3 NPs, and chitosan, a new electrochemical nanosensor platform (MWCNT/Fe 2 O 3 @chitosan NC) was fabricated based on the synergistic effect of MWCNTs, and Fe 2 O 3 NPs dispersed in chitosan NC.…”
Section: Introductionmentioning
confidence: 99%